The Palgrave Handbook of International Energy Economics - Hafner, Manfred; Luciani, Giacomo (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access handbook is distinguished by its emphasis on international energy, rather than domestic energy policies or international geopolitical aspects. Addressing key topics such as energy production and distribution, renewables and global energy trends, regional case studies and emerging areas such as the digitalization of energy and energy transition, this handbook provides a major new contribution to the field of international energy economics. Professor Manfred Hafner teaches economics and (geo)-politics of international energy at the SciencesPo Paris School of International Affairs (PSIA) and at The Johns Hopkins University School of Advanced International Studies (SAIS-Europe). Until recently he directed the "Geopolitics and Energy Transition" research program at the Fondazione Eni Enrico Mattei (FEEM). He also runs his own energy strategy consultancy with which he has over the last decades extensively advised governments, international organizations and the energy industry. Professor Giacomo Luciani leads the Master in International Energy at the Paris School of International Affairs, Sciences Po, which he established in 2011. He is also adjunct professor of interdisciplinary studies at the Graduate Institute of International and Development Studies in Geneva; and Visiting Professor in the Master in Commodity Trading of the Graduate School of Economics and Management of the University of Geneva. This book was published open access with the support of Eni.